Kepemimpinan Transformasional Pengasuh Pondok Pesantren IMBOS Pringsewu di Era 5.0 - Ahmad Nur Huda Huda; Eti Hadiati; Oki Dermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pesantren, as the oldest Islamic educational institution in Indonesia, plays a strategic role in shaping character-driven generations in the era of Society 5.0. Therefore, it requires adaptive and visionary leadership to remain relevant amidst the demands of digitalization. This study aims to describe the transformational leadership model of the caregivers/kiai at the IMBOS Islamic Boarding School in Pringsewu, focusing on role modeling, inspirational motivation, intellectual stimulation, and individualized consideration. Using a descriptive qualitative approach with a single case study, data were collected thru in-depth interviews, observation, and documentation, and then analyzed using the interactive model of Miles, Huberman, and Saldana. Informants were selected purposively, while data validity was strengthened thru source, technique, and time triangulation. The findings indicate that the caregivers/kiai at the IMBOS Islamic boarding school practiced transformational leadership integrated with Islamic spiritual values and digital innovation. Exemplary behavior is reflected in discipline, integrity, and moral consistency; inspirational motivation is realized thru the delivery of an educational vision that is considered an act of worship; intellectual stimulation is evident in the digitalization of pesantren management, such as cashless systems, computer-based learning, digital attendance, online student admissions, and digital libraries; while individual attention is seen in character development, empathetic support, and the development of teacher and staff competencies. This research yielded a novel finding: Transformational Digital Leadership of Kyai in Islamic Boarding School 5.0, a boarding school leadership model that adaptively and visionarily integrates Islamic values, humanism, and digital transformation.